Significant floral changes across the Permian-Triassic and Triassic-Jurassic transitions induced by widespread wildfires - Zhang, Peixin; Yang, Minfang; Jiang, Zhongfeng; Zhou, Kai; Xu, Xiaotao; Chen, Huijuan; Zhu, Xuran; Guo, Yanghang; Ye, Huajun; Zhang, Yuchan; Shao, Longyi; Lu, Jing (Frontiers in Ecology and Evolution, 2023)
Wildfires are a major source of perturbations to the Earth's system and have important implications for understanding long-term interactions between the global environment, climate, and organisms. In this study, current evidence for global warming, wildfires, and floral changes across the Permian-Triassic (P-T) and Triassic-Jurassic (T-J) transitions were reviewed, and their relationships were discussed. Available evidence suggests that global plant community turnover and the decline in plant diversity across the P-T and T-J boundaries were primarily driven by widespread wildfires. The Siberian Large Igneous Province and Central Atlantic Magmatic Province released large amounts of isotopically light CO2 into the atmospheric system, contributing to global warming and increased lightning activity. This ultimately led to an increase in the frequency and destructiveness of wildfires, which have significantly contributed to the deterioration of terrestrial ecosystems, the turnover of plant communities, and the decline in plant diversity. Furthermore, frequent wildfires also constitute an important link between land and ocean/lake crises. Large amounts of organic matter particles and nutrients from the weathering of bedrock after wildfires are transported to marine/lake systems through runoff, contributing to the eutrophication of surface water and the disappearance of aerobic organisms, as well as hindering the recovery of aquatic ecosystems. These wildfire feedback mechanisms provide an important reference point for environmental and climatic changes in the context of current global warming. Therefore, the interplay between global warming, wildfires, and biological changes and their feedback mechanisms needs to be fully considered when assessing current and future risks to the Earth's surface systems.